Epidemiology of cerebral venous sinus thrombosis and cerebral venous sinus thrombosis with thrombocytopenia in the United States, 2018 and 2019 - Amanda B. Payne; Alys Adamski; Karon Abe; Nimia L. Reyes; Lisa C. Richardson; William Craig Hooper; Laura A. Schieve (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background Population‐based data about cerebral venous sinus thrombosis (CVST) are limited. Objectives To investigate the epidemiology of CVST in the United States. Patients/Methods Three administrative data systems were analyzed: the 2018 Healthcare Cost and Utilization Project National Inpatient Sample (NIS) the 2019 IBM MarketScan Commercial and Medicare Supplemental Claims Database, and the 2019 IBM MarketScan Multi‐state Medicaid Database. CVST, thrombocytopenia, and numerous comorbidities were identified using the International Classification of Diseases, Tenth Revision, Clinical Modification codes. Incidence rates of CVST and CVST with thrombocytopenia were estimated (per 100,000 total US population [NIS] and per 100,000 population aged 0 to 64 years covered by relevant contributing health plans [MarketScan samples]). Comorbidity prevalence was estimated among CVST cases versus total inpatients in the NIS sample. Recent pregnancy prevalence was estimated for the Commercial sample. Results Incidence rates of CVST in NIS, Commercial, and Medicaid samples were 2.85, 2.45, and 3.16, respectively. Incidence rates of CVST with thrombocytopenia were 0.21, 0.22, and 0.16, respectively. In all samples, CVST incidence increased with age; however, peak incidence was reached at younger ages in females than males. Compared with the general inpatient population, persons with CVST had higher prevalences of hemorrhagic stroke, ischemic stroke, other venous thromboembolism (VTE), central nervous system infection, head or neck infection, prior VTE, thrombophilia, malignancy, head injury, hemorrhagic disorder, and connective tissue disorders. Women aged 18 to 49 years with CVST had a higher pregnancy prevalence than the same‐aged general population. Conclusions Our findings provide recent and comprehensive data on the epidemiology of CVST and CVST with thrombocytopenia.